2005
DOI: 10.1016/j.envsoft.2004.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Long-run models of oil stock prices

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 9 publications
5
18
0
1
Order By: Relevance
“…Furthermore, all the models had the residuals organized as white noise (p > 0.33) and were stationary with the mean and trend not significantly different from 0 (p > 0.12 and p > 0.17, respectively). The fulfillment of the assumptions and the agreement with the results of other studies investigating petroleum drilling (Iledare and Pulsipher, 1997;Lanza et al, 2005;Rao, 2000;Ringlund et al, 2008;Walls, 1994) suggest that the models can be considered as correct. Furthermore, there is no evidence that different models have different likelihoods; therefore, the futures built using the five models can occur and are equally likely (Supplementary data e Table 2).…”
Section: The Development Of the Set Of Futuressupporting
confidence: 63%
“…Furthermore, all the models had the residuals organized as white noise (p > 0.33) and were stationary with the mean and trend not significantly different from 0 (p > 0.12 and p > 0.17, respectively). The fulfillment of the assumptions and the agreement with the results of other studies investigating petroleum drilling (Iledare and Pulsipher, 1997;Lanza et al, 2005;Rao, 2000;Ringlund et al, 2008;Walls, 1994) suggest that the models can be considered as correct. Furthermore, there is no evidence that different models have different likelihoods; therefore, the futures built using the five models can occur and are equally likely (Supplementary data e Table 2).…”
Section: The Development Of the Set Of Futuressupporting
confidence: 63%
“…Moreover, Faff and Brailsford (1999), Sadorsky (1999Sadorsky ( , 2001 found that the oil prices volatility have asymmetric effects on stocks. Among others who contributed in this area are, Aleisa et al (2003), , El-Sharif et al (2005), Lanza et al (2005), Anorou and Mustafa (2007), Basher et al (2010), and Park and Ratti (2008). Some of these studies used data from emerging economies such as Canada, Europe, US and UK.…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, the movement of oil future prices explained oil companies' stock price shocks. Lanza et al (2005) used VAR/VECM models to research the relationships among six large oil companies, various stock markets, and the spread of crude oil future and spot price. He found that the greater the spread, the higher the oil companies' stock prices.…”
Section: Literature Reviewmentioning
confidence: 99%